Enforcing Laws Against Illegal Gold Mining through the Lens of Islamic Criminal Law: A Case Study of Jambur Tarutung Kotanopan - Tagor Indra Mulia Lubis; Ramadani (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2025)
Illegal gold mining (pertambangan emas tanpa izin, PETI) in Jambur Tarutung, Kotanopan, presents complex legal, socio-economic, and environmental challenges. This study examines the enforcement of criminal law against illegal gold mining in the region and explores how Islamic criminal law can provide a complementary framework for addressing such issues. Using an empirical juridical approach, this research integrates normative analysis of relevant legal provisions - particularly Law No. 3 of 2020 on Mineral and Coal Mining - with field data gathered through in-depth interviews, observations, and document analysis involving law enforcement officials, community leaders, religious scholars, and affected residents. Findings reveal that law enforcement remains largely ineffective due to weak supervision, limited institutional capacity, socio-political interference, and the dependence of local communities on illegal mining as an economic livelihood. From an Islamic criminal law perspective, these activities constitute jarimah ta?z?r involving fasad (corruption and destruction), warranting discretionary sanctions by the ulil amri that combine punitive and restorative measures. This study argues for an integrative enforcement model that merges positive law with maq??id al-shar??ah, emphasizing ecological restoration, community empowerment, and moral-spiritual reform. Such an approach promotes sustainable resource governance while fostering social justice and collective environmental responsibility.